(untitled) (American Journal of Islam and Society, 1987)
The Association of Muslim Social Scientists (AMSS) held its Sixteenth Annual Conference at the ISNA headquarters in Plainfield, Indiana, October 9-11, 1987. Registration listed about 200 participants from the United States, Canada, the United Kingdom, Pakistan, Trinidad, and other countries. The inaugural session on October 9 provided a hospitable setting for camaraderie. Eloquent and spirited speeches by Iqbal Unus, Conference Chairman; lbrahim Syed, AMSE Program Chairman; and Mushtaqur Rahman, AMSS Program Chairman, set the stage for the conference and the sessions. Chaired by Salahuddin Malik, AMSS Vice-president, the first session on Political Science was held on Friday evening after Salat-ul Maghrib. Hashem Al-Jaseem of the University of California was the first to present his paper on Islam and Politics. He was followed by Taysir Nashif of Essex County College, who pleaded for a Nuclear Free Zone in the Middle East. Louay Safi of Wayne State University concluded the session with his presentation of War and Peace in Islam. This session was so lively and discussions so absorbing that no time was left for the following session scheduled for the same evening. Conferees preferred to postpone the second session rather than to conclude the discussions. It was heartening that every conferee maintained the Islamic tradition of conducting debates in a spirit of good humor, disagreeing without being disagreeable. The first full day of the conference, Saturday, October 10, began with a Tilawat-e-Quran, and a session on Education. Chaired by M.A.W. Fakhri of Chicago State University, the session had two presentations. Hakim Rashid of Howard University opened the session with his paper on “SocializatiodEducation of Muslim Children in America”. He was followed by Nimat Hafez Barzangi of Cornell University, who presented her paper on “Perceptions of the Islamic Belief System: The Muslims in North America. Following the session on education, two concurrent sessions were held on Sociology and History dealing with Muslim minorities. This was the first time the strategy of concurrent sessions was ever tried in the AMSS. The sociology session Chairperson, Ilyas Baynus of the State University of New York, first invited ...